Developmental programming of vascular dysfunction by prenatal and postnatal zinc deficiency in male and female rats - Mendes Garrido Abregú, Facundo (2018)
Micronutrient malnutrition during intrauterine and postnatal growth may program cardiovascular diseases in adulthood. We examined whether moderate zinc restriction in male and female rats throughout fetal life, lactation and/or postweaning growth induces alterations that can predispose to the onset of vascular dysfunction in adulthood. Female Wistar rats were fed low- or control zinc diets from pregnancy to offspring weaning. After weaning, offspring were fed either a low- or a control zinc diet until 81 days. We evaluated systolic blood pressure (SBP), thoracic aorta morphology, nitric oxide (NO) system and vascular reactivity in 6- and/or 81-day-old offspring. At day 6, zinc-deficient male and female offspring showed a decrease in aortic NO synthase (NOS) activity accompanied by an increase in oxidative stress. Zinc-deficient 81-day-old male rats exhibited an increase in collagen deposition in tunica media, as well as lower activity of endothelial NOS (eNOS) that could not be reversed with an adequate zinc diet during postweaning life. Zinc deficiency programmed a reduction in eNOS protein expression and higher SBP only in males. Adult zinc-deficient rats of both sexes showed reduced vasodilator response dependent on eNOS activity and impaired aortic vasoconstrictor response to angiotensin-II associated with alterations in intracellular calcium mobilization. Female rats were less sensitive to the effects of zinc deficiency and exhibited higher eNOS activity and/or expression than males, without alterations in SBP or aortic histology. This work strengthens the importance of a balanced intake of micronutrients during perinatal growth to ensure adequate vascular function in adult life.